Understanding Health Research Ethics in Nepal. Issue 3 (3rd February 2016) - Sharma, Jeevan Raj; Khatri, Rekha; Harper, Ian
Abstract: Unlike other countries in South Asia, in Nepal research in the health sector has a relatively recent history. Most health research activities in the country are sponsored by international collaborative assemblages of aid agencies and universities. Data from Nepal Health Research Council shows that, officially, 1, 212 health research activities have been carried out between 1991 and 2014. These range from addressing immediate health problems at the country level through operational research, to evaluations and programmatic interventions that are aimed at generating evidence, to more systematic research activities that inform global scientific and policy debates. Established in 1991, the Ethical Review Board of the Nepal Health Research Council (NHRC) is the central body that has the formal regulating authority of all the health research activities in country, granted through an act of parliament. Based on research conducted between 2010 and 2013, and a workshop on research ethics that the authors conducted in July 2012 in Nepal as a part of the on‐going research, this article highlights the emerging regulatory and ethical fields in this low‐income country that has witnessed these increased health research activities. Issues arising reflect this particular political economy of research (what constitutes health research, where resources come from, who defines the research agenda, culture of contract research, costs of review, developing Nepal's research capacity, through to the politics of publication of data/findings) and includes questions to emerging regulatory and ethical frameworks.